2022
DOI: 10.1177/10526846221134010
|View full text |Cite
|
Sign up to set email alerts
|

Role of School Principals’ Technology Leadership Practices in Building a Learning Organization Culture in Public K-12 Schools

Abstract: A principal’s technology leadership (TL) practices can facilitate information and communication technologies (ICT) integration into K-12 schools, alongside a drastic change in teachers' organizational behaviors to accompany this technological and cultural transformation process. However, there is little evidence of which TL practices contribute to such a holistic change in school culture; that is, the learning organization (LO) culture stimulating teachers' individual and collective professional learning orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
1
8
0
2
Order By: Relevance
“…This implies that effectively implementing the principal's technology leadership in schools can foster an environment where teachers actively seek information, communicate, and collaborate, leveraging technology tools as facilitators. In addition, these findings align with previous studies highlighting the impact of principals' digital leadership on cultivating a digital learning culture and integrating technology into instruction [26,45,47,48,68,120].…”
Section: Direct Effectsupporting
confidence: 89%
See 2 more Smart Citations
“…This implies that effectively implementing the principal's technology leadership in schools can foster an environment where teachers actively seek information, communicate, and collaborate, leveraging technology tools as facilitators. In addition, these findings align with previous studies highlighting the impact of principals' digital leadership on cultivating a digital learning culture and integrating technology into instruction [26,45,47,48,68,120].…”
Section: Direct Effectsupporting
confidence: 89%
“…Similarly, McConnell et al [70], observed that virtual Professional Learning Communities (PLCs) utilizing video-conferencing tools necessitated teacher technology skills, fostering relationships and collaboration among teachers to enhance the teaching and learning process in the 21st century. Furthermore, several studies consistently emphasized the impact of school culture, specifically in terms of organization learning, on teachers' technological, pedagogical, and content knowledge (TPACK), team communication, and support learning mediated by technology tools teachers' technology integration capabilities in the instruction [48,[62][63][64][65][66][67][68]86,87,[89][90][91].…”
Section: Direct Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Eğitim yöneticilerinin görüşleri doğrultusunda yapılan çalışmaya göre standartların Türkiye'de uygulanabileceği ancak bazı düzenlemelere ihtiyaç duyulduğu sonucuna ulaşılmıştır. Banoğlu (2011) çalışmasında ISTE (2002 standartları doğrultusunda ilkokul, ortaokul ve lise okul yöneticilerinin teknolojik liderlik yeterliklerinin belirlenmesi amacıyla hazırlanan ölçeğin geçerlik ve güvenirlik çalışmalarını yapmıştır.…”
Section: ______________________________________________unclassified
“…Araştırmaya göre müdürlerin ISTE, NETS-A standartlarından vizyoner eğitim teknolojisi liderliği sağlamaya hazırlıklı olmadıkları tespit edilmiştir. Yine Banoğlu (2011) araştırmasında "Okul Müdürlerinin Teknoloji Liderliği Ölçeği"ni kullanarak okul müdürlerinin "önemli oranda" teknoloji liderliği yeterliğine haiz olduğu ancak "liderlik ve vizyon" boyutunda en düşük yeterliğe sahip olduğunu belirlemiştir. Ancak alanyazında bu durumun tam aksi sonuçlar da mevcuttur.…”
Section: ______________________________________________unclassified